Pengembangan Paket Pembelajaran Bahasa Arab dengan Model Dick Carey and Carey - Nur Khotimah (At- Ta'lim : Jurnal Pendidikan, 2015)
This type of learning is develop based on examine of technology learning of refer to design dick, Carey of Carey (2011). Procedure of developing is not only done in nine steps but also packet of learning which is development figured. Arabic language subject to seventh student, Second semester consists of 3 part that is matter of the studi part finder educator and participant of learning. Packet development process of learning is done passing through five stages: first step decide the subject which will be develop. Second step, identify syllabus of the subject which will develop. Third, formulate steps developing. Firfth, test and revise developing product. The result test expert stage of study in excelent result. Result test expert design and learning instrument to volume of learn are in good result, part finder educator and part finder learning participant are in good category, the result of personal test volume of study exist of 6 mistakes in the clicking, seven mistakes in the punctuation mark, three mistakes in the explaining picture. Result test of small group matter of study and scout participant of study are in good category, the result test of observation matter of study performance of participant is in good category, the result pre test and pos test with twenty emancipations rank and standart significant 0,05 are gotten observe is bigger than T table, that is 20,5 called matter of study which is used effective. The strength of packet learning which has arranged: (1) packet learning is arranged system . (2) packet learning can be influanced interest student to study. (3) Packet learning can be facilitated learning process in tjhe class, whereas weakness this packet is arranged based on characteristic of participant of MTs Darul Ulum Kraksaan Probolinggo. Suggestion which mimicries is: (1) Before using matter of learn, expert learning participant read first utilization instruction. (2) Matter of study Arabic language can be used in Mts Drul Ulum only. (3) If the matter is used learning participant next level, necessary remove analyze needed to study.